Tren Hidup Sehat Melalui Interaksi Sosial di Tiktok: Efektivitas Konten Kesehatan Terhadap Perubahan Gaya Hidup - Aryanto, Tiara Nisa; Irwansyah (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
This research examines the trend of healthy living through social interaction on the mobile-based social media application TikTok which is supported by artificial intelligence (AI), and the effectiveness of health content in changing people's lifestyles. Using a qualitative and case study approach, it was found that engaging short-form content delivered by credible personalities, supported by AI technology such as recommendation algorithms and user data analysis, motivates users to adopt healthy habits such as a good diet and moderate exercise. Social interaction through features on TikTok strengthens the virtual community that supports this motivation. However, the risk of spreading hoaxes and social pressure remain challenges that need to be addressed. These results emphasize the importance of collaboration between content creators, platforms, health professionals, governments, and the use of AI technology to provide accurate and educative information for a positive and sustainable impact on healthy lifestyles.